Pengaruh Imbangan Protein Kasar dan Total Digestible Nutrients pada Pakan yang Berbeda Terhadap Pemanfaatan Energi Pakan pada Domba Lokal - Nugroho, D.; Purnomoadi, A.; Riyanto, E. (Universitas Sebelas Maret (UNS), 2013)
Energy utilization is affected by protein-energy balance in the feed. The purpose of this studywas to determine the optimum balance of crude protein (CP) and total digestible nutrients (TDN) in a feed efficiency on the native sheep, by looking at the ability of the utilization of energy from the feed. 24 male native sheep with an average of initial body weight around 18±3.1 kg (CV=17.15%), were used and designed with a completely randomized design (CRD) into 6 dietary treatments of complete feed: Treatment 1 (CP 18.84% and 61.56% TDN), Treatment 2 (CP 16.29% and 66.51% TDN), Treatment 3 (CP 19.94% and 60.29% TDN), Treatment 4 (CP 19.40% and 67.31% TDN), Treatment 5 (CP 20.88% and 60.47% TDN), Treatment 6 (CP 20.12% and 63.05% TDN). Data were analyzed by analysis of variance. Results of DM intake between treatments were not significantly different (P>0.05). The average intake of DM of the study was 775.6 g/day. Energy intake in each treatment was not significantly different (P>0.05) (14.27±1.7 MJ/day). Different ratio of CP and TDN on digested amount of energy in each treatment were not significantly different (P>0.05). Average metabolized energy in native sheep in this study was 6.28 ± 0.9 MJ/day (P>0.05). Conclusion from this research is the different balance of CP and TDN in this study do not have any impact on energy utilization and body weight gain (ADG) of native sheep.Key words: sheep, ratio of CP and TDN, energy feed utilization